Leaf Trait Variability and CSR Strategy Shifts in Mediterranean Woody Species along an Edaphic Gradient - Khalil Kadaoui; Jalal Kassout; Vladimiro Andrea Boselli; Soufian Chakkour; Abdelouahab Sahli; Mhammad Houssni; Hassan Bouziane; Mohammed Ater (Ecologies)
Plant species in Mediterranean ecosystems are expected to exhibit diverse responses to environmental stresses such as climate aridity and challenging soil conditions by adopting various functional strategies. However, intraspecific variability at the local scale has received insufficient attention in the study of CSR strategies. This study aims to evaluate intraspecific variability in leaf traits and CSR strategies of seven woody species growing on ultramafic and non-ultramafic soils in the Beni Bousera region of Northern Morocco. We first conducted a physicochemical analysis to assess differences in soil composition between the two sites. Subsequently, we measured leaf fresh weight, leaf dry weight, and leaf area and calculated CSR strategies for 10 individuals per species. The results revealed significant differences between the two soil types, primarily driven by a moderate serpentine effect characterized by a Ca:Mg ratio <1 in the ultramafic site, along with distinct soil texture. In response to these challenging conditions, we observed substantial intraspecific variability in leaf traits, accompanied by shifts in CSR strategies for certain species. At the ultramafic site, Quercus coccifera adopted an S strategy, while Cistus salviifolius exhibited an S/SC strategy. Lavandula stoechas and Teucrium fruticans displayed notable interindividual variability, whereas Cistus atriplicifolius, Phillyrea latifolia, and Erica arborea maintained consistent strategies across both sites. Our research contributes to the enrichment of CSR databases and highlights the applicability of the CSR strategy framework at the local, intraspecific level, offering a valuable foundation for future ecological studies and plant conservation efforts. Moreover, investigating intraspecific variability in leaf traits and CSR strategies enhances our understanding of plant adaptation mechanisms in extreme environments such as Mediterranean serpentine soils.